Probiotic modulation of the gut bacterial community of juvenile Litopenaeus vannamei challenged with Vibrio parahaemolyticus CAIM 170 - Irasema E Luis-Villaseñor; Domenico Voltolina; Bruno Gomez-Gil; Felipe Ascencio; Ángel I Campa-Córdova; Juan M Audelo-Naranjo; Olga O Zamudio-Armenta (Latin American Journal of Aquatic Research, 2015)
The protective effects of two probiotic mixtures was studied using the fingerprints of the bacterial community of Litopenaeus vannamei juveniles exposed to probiotics and challenged with Vibrio parahaemolyticus CAIM 170. Fingerprints were constructed using 16S rRNA gene and the PCR-SSCP (Single strand conformation polymorphism) technique, and the probiotics used were an experimental Bacillus mixture (Bacillus tequilensis YC5-2 + B. endophyticus C2-2 and YC3-B) and the commercial probiotic Alibio. The DNA for PCR-SSCP analyses was extracted directly from the guts of shrimps treated for 20 days with the probiotics and injected with 2.5*10(5) CFU g-1 of V. parahaemolyticus one week after suspension of the probiotic treatment. Untreated shrimps served as positive (injected with V. parahaemolyticus) and negative (not injected) controls Analysis of the bacterial community carried out after inoculation and 12 and 48 h later confirmed that V. parahaemolyticus was present in shrimps of the positive control , but not in the negative control or treated with the probiotic mixtures. A significant difference in the diversity of the bacterial community was observed between times after infection. The band patterns in 0-12 h were clustered into a different group from that determined after 48 h, and suggested that during bacterial infection the guts of whiteleg shrimp were dominated by gamma proteobacteria represented by Vibrio sp. and Photobacterium sp. Our results indicate that the experimental and the commercial mixtures are suitable to modulate the bacterial community of L. vannamei and could be used as a probiotic to control vibriosis in juvenile shrimp.